Pemberdayaan Masyarakat Tani Di Desa Maria Kabupaten Bima Melalui Diversifikasi Olahan Stik Berbasis Labu Kuning - Aris Munandar; Firmansyah Kusumayadi; Muhsanan Muhsanan; Muhajirin Muhajirin; M. Syukur Dwiriansyah (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2021)
This Community Service activity aims to:  Provide training on making pumpkin-based products in Maria Village, Wawo District, Bima Regency. Find out the response of the Maria Village community to training on pumpkin-based stik labu. This community service activity method uses the lecture method, demonstration, question and answer method, and exercises in making stik labu. This training involves student members of the Real Work Lecture accompanied by a companion lecturer from the Management Study Program with participants from housewives and the community in Maria Village. The results of the pumpkin steak making training conducted by the community, especially IRT in Maria Village, are the results of the evaluation of the pumpkin steak made by the trainees, in general, are in the good category with an average success of 70%,  the response from the community to the implementation of the training stick labu making is very good, seen from the attendance reaching 100% and following the activities from beginning to end.